2011
DOI: 10.21161/mjm.23810
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic investigation of endophytic Fusarium strain producing antimicrobial metabolite isolated from Himalayan Yew Bark

Abstract: An endophytic fungus, Fusarium sp. was isolated from yew bark of eastern Himalaya. Ethyl acetate extract from its fermentation broth displayed considerable antimicrobial activity against three Gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis and Staphylococcus epidermidis), three Gram-negative bacteria (Klebsiella pneumoniae, Escherichia coli and Shigella flexneri) and two pathogenic fungi (Candida albicans and Candida tropicalis). The metabolite showed highest inhibition zone against K. pneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…However, the mechanisms of inhibition in colony growth of the tested fungi were not addressed in our studies. This was similar to the investigation of Tayung et al [17] investigated an endophytic fungus Fusarium sp. with highest antimicrobial and antioxidant analysis isolate from India.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the mechanisms of inhibition in colony growth of the tested fungi were not addressed in our studies. This was similar to the investigation of Tayung et al [17] investigated an endophytic fungus Fusarium sp. with highest antimicrobial and antioxidant analysis isolate from India.…”
Section: Discussionsupporting
confidence: 88%
“…First and foremost pharmaceutical applied drug Taxol, an anticancer drug was derived from Taxus, a gymnosperm is an important anticancer plant. Several endophytic fungi isolated from Taxus spp., worldwide have been reported to produce important bioactive metabolites [16,17]. This current investigation is focused to produce the pigmented crude secondary metabolites and purify a bioactive compound through the antioxidant assessment which could be taken for anticancer applications by in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…from different plant as broad host range endophyte (Shahasi et al, 2006 ; Changhong et al, 2010 ) was reported by many authors and there were numbers of research articles reporting Fusarium sp. as beneficial biocontrol agent and a source of bioactive molecules (Shweta et al, 2010 ; Tayung et al, 2011 ). The biodiversity analysis using Shannon-Weiner Diversity Index confirms that rice samples harbor a higher diversity than maize.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had reported the antibacterial activity of endophytic fungi belonging to Fusarium genera isolated from other medicinal plants such as Ophiopogon japonicus, 10 Aqularia sinensis 29 and Taxus baccata. 30 The genera Fusarium has been reported to be a rich source of diverse compounds with antibacterial activities. Beauvericin, isolated from F. oxysporum, which is associated with Cinnamomum kanihirai, was reported toxic against methicillin-resistant S. aureus and B. subtilis.…”
Section: Discussionmentioning
confidence: 99%